„Zamknięte, uszkodzenia spowodowane nalotem”. Działalność aptek w Festung Breslau (I 1945 – V 1945) - Rosner-Leszczyński, Kacper (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2022)
The article describes the operation of pharmacies in Wrocław during the battle of Festung Breslau (1945). Faced with the evacuation of the civilian population and the advance of Red Army troops, the District Pharmaceutical Chamber (Bezirksapotheker-kammer) reduced the pharmacies subordinate to it and tried to regulate the operation of the remaining ones. Soviet air raids on the city were a considerable hindrance, and a shortage of basic medicines was also felt. The problems faced by pharmacists in Wrocław are illustrated by the published memoirs of Johannes (Hanns) Hoffmann.
Keywords: regionalizm; region; Śląsk; Polska; Czechy; Niemcy; czasopismo regionalne; czasopismo historyczne